Realidades múltiplas: o fantástico em Jorge Luis Borges e Mariana Enríquez - Marques, Thiago Moreira (2023)
Since the second half of the twentieth century, fantastic literature has found its way among academic research and writings. Besides this literature, other concepts cover different yet similar aesthetic experiences, like the uncanny, the weird, the eerie and the magic realism. The following thesis intends to analyze four short stories written by two Argentinian authors, Jorge Luis Borges and Mariana Enríquez, through the lens of fantastic and magic realism theories. The selected short stories are O Zahir and O Aleph, by Jorge Luis Borges; and O menino sujo and Sob a água negra, by Mariana Enriquez. This study aims to demonstrate how both authors, who are understood as fantastic literature writers, present similarities but also differences in the way they approach the same topics. Besides that, it is also approached how those two authors depict the city of Buenos Aires, and if this description creates a fantastic effect in their work. This is a qualitative study, and the methodology is bibliographical.